Fuelling Success : How Learning – Driven Innovation Supercharges SMEs’ Performance - Kaur, Gurpreet Pal; Saini, Harish; Bedi, Harpreet Singh (Prabandhan: Indian Journal of Management, 2025)
Purpose : The present study examined the impact of learning orientation on the performance outcomes of small- and medium-sized enterprises (SMEs), focusing on innovativeness as a mediating factor. Methodology : A structured questionnaire was used to collect data from 413 SMEs in Punjab, India, on learning orientation, innovativeness, and business performance. Structural equation modeling was applied to test the hypotheses. Findings : The study revealed a positive relationship between learning orientation and business performance in SMEs. Additionally, innovativeness has been identified as a significant mediator in this relationship, highlighting that learning orientation fosters innovative practices that, in turn, improve business performance. Practical Implications : This study provided valuable guidance for management practitioners and academicians. The study revealed how learning orientation impacted business performance through innovativeness. Originality : The study offered a perspective on how SMEs could strategically use learning orientation to improve their overall performance and capacity for innovation.